Fisheries data: could it be caught by mobile apps? - Haughton, Milton (Technical Centre for Agricultural and Rural Cooperation, 2015)
Milton Haughton, Executive Director of the Caribbean Regional Fisheries Mechanism (CRFM), discusses the importance of accurate fisheries data, why this is so difficult to collect and the need for new models in collecting, validating and distributing the data. He also talks about the future role of mobile apps in filling this role